Measurements in Wound Healing Science and Practice - Mani, Raj.; Romanelli, Marco.; Shukla, Vijay. (Springer London : Imprint: Springer, 2013)
The lack of evidence-based medicine for the treatment of complex chronic wounds is apparent to most working in this challenging area. With increased longevity in most Western countries there is an increased prevalence of chronic diseases and consequently chronic wounds, especially the common venous and diabetic foot ulcer. There is therefore an urgent need to provide an evidence-based approach to the management of chronic wounds: an essential prerequisite is to have accurate measurements in the science of wound healing. Measurements in Wound Healing: Science and Practice covers the common chronic wounds from venous leg ulcers and diabetic foot disease to pressure ulcers. Chapters on topics such as burns and scarring are discussed alongside the all important topics of research in this area, randomized controlled trials and modeling. The editors have brought together a team of true experts of numerous disciplines from basic science to clinical medicine.The book is equally valuable to the specialist as well as those developing an interest in the management of wound healing.